Eu3+-activated CaGa2O4 wide band gap (WBG) material for solar blind UV conversion: Fluorescence and photo-conductivity performance - Rai M.; Singh S.K.; Mishra K.; Shankar R.; Srivastava R.K.; Rai S.B. (My University, 2025)
Herein, we have probed a wide band gap material, CaGa2O4 co-doped with Eu3+/Na+, which is fairly transparent (≥95%) in the visible region and efficiently absorbs solar blind UV radiation. Importantly, the absorbed UV energy can be realized both in terms of fluorescence and photoconductivity as well. X-ray diffraction studies confirmed that CaGa2O4 exhibits two orthorhombic polymorphs: CaO·Ga2O3 I (major) and CaO·Ga2O3II (minor). Vibrational spectroscopy provided the first quantitative insight into the phonon frequency of the material. Upon UV illumination the host itself gives UV-blue and red emissions due to band to band and trap level transitions, respectively. (no additional dopant or activator ion were present). A substantial overlap between the emission spectrum of the host and the excitation spectrum of Eu3+; decrease in emission intensity and decay time (8.82 μs from 9.2 μs) of the host emission, after Eu3+ doping; and evolution of a short rise-time (∼10 μs) in decay curve of Eu3+ revealed that the host efficiently transfers its energy to the Eu3+ ions. Co-doping of Na+ further enhances the emission intensity (∼7 times), decay time and rise-time of the Eu3+ emission. Likewise the intrinsic behavior of Ga2O3 this material also shows significant transient photoconductivity under UV illumination, photocurrent is of the order of μA, but with slow time constant ∼40 min. Thus, the excellent optical properties prove to be superior for photoconductivity for UV-to-visible converter applications. Such WBG optical materials can be coupled to silicon-based commercial detectors for their wide use in areas ranging from invisible flame sensing to UV astronomy. This journal is © the Partner Organisations 2014.